2013
DOI: 10.1186/ar4130
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and the promise of antigen-specific therapy in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic inflammatory disease resulting from an autoimmune response to self-antigens, leading to inflammation of synovial tissue of joints and subsequent cartilage and bone erosion. Current disease-modifying anti-rheumatic drugs and biologic inhibitors of TNF, IL-6, T cells and B cells block inflammation nonspecifically, which may lead to adverse effects, including infection. They do not generally induce long-term drug-free remission or restoration of immune tolerance to self-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 100 publications
0
31
0
Order By: Relevance
“…Increasing evidence has shown that DCs may be attractive targets for the treatment of autoimmune diseases, such as RA (36,37). For instance, injection of immature DCs attenuates CIA by inducing in vivo expansion of CD49b + regulatory T cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that DCs may be attractive targets for the treatment of autoimmune diseases, such as RA (36,37). For instance, injection of immature DCs attenuates CIA by inducing in vivo expansion of CD49b + regulatory T cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…This combination of DCreg with citrullinated peptides was given the name Rheumavax, and patients received a single dose intradermally. Citrullinated self-Ags have emerged as a major group of post-translationally modified auto-Ags in RA and are found in inflamed RA joints [56]. As in the autoimmune diabetes trial at the University of Pittsburgh, the vaccine was well-tolerated and no adverse effects were observed.…”
Section: Current Progressmentioning
confidence: 99%
“…This phase I study assessed the safety of repetitive intradermal administration of tolerogenic DCs in adult type 1 diabetes (T1D) patients. A second phase I study has been conducted in rheumatoid arthritis (RA) patients treated with a single intradermal injection of autologous DCs cultured with an inhibitor of (NF-κB) signaling (BAY 11-7082) and pulsed with citrullinated peptides [87]. Both treatments were safe and well tolerated and paved the way to developing clinical studies to test the efficacy of tolerogenic DC immunotherapy in T1D and RA and after kidney transplantation.…”
Section: Dcs As Tolerogenic Cell Productmentioning
confidence: 99%